Irradiation at Ultra-High (FLASH) Dose Rates Reduces Acute Normal Tissue Toxicity in the Mouse Gastrointestinal System - Ruan, Jia-Ling; Lee, Carl; Wouters, Shari; Tullis, Iain D C; Verslegers, Mieke; Mysara, Mohamed; Then, Chee Kin; Smart, Sean C; Hill, Mark A; Muschel, Ruth J; Giaccia, Amato J; Vojnovic, Borivoj; et al. (International journal of radiation oncology, biology, physics, 2021)
Preclinical studies using ultra-high dose rate (FLASH) irradiation have demonstrated reduced normal tissue toxicity compared with conventional dose rate (CONV) irradiation, although this finding is not universal. We investigated the effect of temporal pulse structure and average dose rate of FLASH compared with CONV irradiation on acute intestinal toxicity. Whole abdomens of C3H mice were irradiated with a single fraction to various doses, using a 6 MeV electron linear accelerator with single pulse FLASH (dose rate = 2-6 × 10 Gy/s) or conventional (CONV; 0.25 Gy/s) irradiation. At 3.75 days postirradiation, fresh feces were collected for 16S rRNA sequencing to assess changes in the gut microbiota. A Swiss roll-based crypt assay was used to quantify acute damage to the intestinal crypts to determine how tissue toxicity was affected by the different temporal pulse structures of FLASH delivery. We found statistically significant improvements in crypt survival for mice irradiated with FLASH at doses between 7.5 and 12.5 Gy, with a dose modifying factor of 1.1 for FLASH (7.5 Gy, P < .01; 10 Gy, P < .05; 12.5 Gy, P < .01). This sparing effect was lost when the delivery time was increased, either by increasing the number of irradiation pulses or by prolonging the time between 2 successive pulses. Sparing was observed for average dose rates of ≥280 Gy/s. Fecal microbiome analysis showed that FLASH irradiation caused fewer changes to the microbiota than CONV irradiation. This study demonstrates that FLASH irradiation can spare mouse small intestinal crypts and reduce changes in gut microbiome composition compared with CONV irradiation. The higher the average dose rate, the larger the FLASH effect, which is also influenced by temporal pulse structure of the delivery.